Optimization of Multi-token circulation with master UAV method in multi-UAV systems for location information sharing - Ülkü, Eyüp Emre; ÜLKÜ, İLAYDA (My University, 2019)
In order to perform smooth and coordinated flights in multi-UAV systems, UAVs (Unmanned Aerial Vehicle) need to know each other's location information. Multi-token circulation method allows UAVs to learn each other's location information in the Flying Ad Hoc Network (FANET) quickly and this information can be updated continuously. In the multi-token circulation method, it is very important to determine how many tokens are used and how these tokens circulate in the FANET depending on the number and deployment of the UAVs. In this paper, we developed a master UAV method to determine number of tokens and circulation of these tokens.
Keywords: Flying ad Hoc Networks (FANET; Location Information Sharing; Multi UAV Systems; Multi-Token Circulation; Unmanned Aerial Vehicle (UAV); Vehicle Routing Problem (VRP)